Development of Lesson Activities in English to Improve Student Profile of Pancasila - Kharisma, Intan Adelia Ngizatul; Putri, Jesica Meidyas (JOURNAL OF TECHNOLOGY, EDUCATION & TEACHING (J-TECH), 2025)
This study aims to develop effective English learning activities to support the improvement of the profile of Pancasila students at the secondary school level. The profile of Pancasila learners includes values such as faith, devotion to God Almighty, noble character, global diversity, mutual cooperation, independence, critical reasoning, and creativity. The development method used is the research and development (R&D) model which includes the stages of needs analysis, activity design, trial, and effectiveness evaluation. The results showed that English learning activities integrated with Pancasila values were able to improve communication skills, critical thinking, and students' ability to work together in a diverse environment. This is reflected in the positive responses of students and teachers who consider learning activities more relevant and applicable in daily life. This study concludes that the integration of Pancasila values in English learning has a positive impact on student character development in accordance with the profile of Pancasila learners.